History of the Azerbaijan state - Nagi, Akif (My University, 2026)
The content of historical science is the historical process. At the heart of historical science is the collection, systematization and generalization of facts. The history of Azerbaijan is an integral part of world history. The prominent Azerbaijani historian A. Bakikhanov writes in his work Gülüstani-İrəm: “History is a silent orator that conveys to successors the condition of their predecessors and explains the paths of progress and decline”.He brings to the attention of people in the clothes of the past the consequences that may arise in the future. Historical science conveys to us the experience of the world... The history of each country is useful for the people living in it. The great philosopher of the West, Hegel, also clarifies the issue. According to his idea, history begins only with the formation of the state and “ends” with the establishment of a “real” state structure. Hegel believed tha the “real” or “ideal” state is a special form of free Organization of persons. The family is the core of the state, the source of life. According to Hegel, in the state, as in nature and the human body, each organ must perform its function. He emphasized that history refers to peoples with a state: “a people (nation) without a state structure has no history”.
(from ancient times to the early middle ages)